Flame retardant study of formalized polyvinyl alcohol fiber coated with melamine formaldehyde resins and the synergistic effect of copper ions. (October 2017) - Jiang, Yan; Zhou, Wanli; Jiang, Mengjin; Liu, Pengqing; Xu, Jianjun
Abstract: The formalized polyvinyl alcohol fibers (PVF fibers) were grafted with acrylic acids after being activated in dilute potassium permanganate solution, and then the grafted PVF fibers (PVF-g-AA fibers) were reacted with melamine formaldehyde (MF) oligomer solution to form flame-retardant coatings on their surface. The coated PVF fibers (PVF-g-AAMF fibers) were further treated with copper sulfate solution for absorbing copper ions to promote their flame retardant performance. The structure of the fibers was characterized by FTIR spectra and SEM photos. The flame-retardant performance of the fibers was evaluated by limiting oxygen index (LOI) and microcalorimeter tests (MCC tests). It is found that MF coatings effectively improved the flame resistance of PVF fibers, but the flame retardant efficiency was not satisfactory. Copper ions have an obvious synergistic effect on the flame resistance of the fibers. SEM photos of char residues, results of TGA and TG-IR revealed that the flame retardance of MF coatings is mainly due to gaseous phase.The effect of copper ions on the thermal decomposition of MF resins was analyzed with pyrolysis-gas chronograms-mass spectrometry (PyGC-MS), and it is found that copper ions catalyzed the thermal decomposition of MF resins, which synchronized the decomposition of MF resins and PVF fibers. Copper ions are also effective in improving the char residues of PVF-g-AAMF fibers. The flame resistance of the fibers was improved dramatically by the synergistic effect between the grafted MF resin and the copper ions.